Obstacles and facilitators to communicating with children about their parents’ mental illness: a qualitative study in a sub‑district of Mpumalanga, South Africa - Lucy Dean; Hadassah Buechner; Bianca Moffett; Meriam Maritze; Louise J. Dalton; Jeffrey R. Hanna; Elizabeth Rapa; Alan Stein; Stephen Tollman; Kathleen Kahn (My University, 2023)
Background Given that common mental disorders are one of the leading causes of disease burden worldwide, it is likely that many children are growing up with a parent or other adult within their family who has anxiety or depression. Parents with a mental illness may not consider it appropriate to discuss their illness with their child, and consequently an absence of communication may lead to stigmatization, shame, misunderstanding their parents’ symptoms, and even blaming themselves. There is a scarcity of research exploring the experiences and perceptions of healthcare professionals about communication with children of parents with mental illness in low-resource and African contexts. Methods A qualitative study using semi-structured interviews with healthcare professionals (n = 15) was conducted within the Bushbuckridge sub-district of Mpumalanga Province, South Africa. Data were analysed using Thematic Analysis. Results Four themes were identified relating to the obstacles around communication with children. These included: (1) finding an appropriate language to describe mental illness, as well as the prevailing cultural explanations of mental illness (2) the stigma associated with mental illness (3) the perceived role of children in society and (4) mental health services and staff skills. Two themes that addressed facilitators of communication about parental mental illness were identified: (1) the potential to increase mental health awareness amongst the broader community through social media, the internet, and general psychoeducation (2) healthcare professionals’ concerns for the wellbeing and future mental health of patients’ children, as well as their hopes for increased mental health awareness amongst future generations. Conclusions This study provides insight into healthcare professionals’ attitudes and perceptions about talking to patients and families within their community about mental illness. The results provide recommendations about possible ways to promote sharing information about a parent’s mental illness with children at an individual and community level. Future research should focus on the collaborative creation of culturally sensitive psychoeducational